The Significance of Al-Ghazali's Thought in Contemporary Islamic Education in Indonesia - Nuryulia, Siti; Futuwatuddin, Muhammad Ibrohim; Gunawan, Agus; Gufron, Iffan Ahmad (Al Hikmah: Journal of Education, 2024)
In Indonesia, the Islamic education system frequently encounters a gap between the requests of the modern curriculum and conventional values. Through Al-Ghazali's considerations of balance and Sufism, a more all encompassing approach to instruction can be realized, coming about in understudies who are not as it were savvy people cleverly, but moreover have respectable character. This article points to analyze the significance of Al-Ghazali's contemplations within the current setting of Islamic instruction in Indonesia, as well as how his standards can be coordinates to confront challenges and strengthen students' character within the modern era. With a expressive approach and writing investigation, this paper shows that Al-Ghazali's contemplations stay important and noteworthy within the arrangement of today's Islamic instruction framework. This research uses a literature review or library research to examine various journal reference sources. The research results appear that there are numerous considerations from Al Ghazali to be connected in today's instruction, such as the part of instructors, educational programs administration or choosing learning strategies.